The Influence of Digitization and Human Resources Competence on the Financial Performance of Pondok Permai Restaurant: Pengaruh Digitalisasi dan Kompetensi SDM terhadap Kinerja Keuangan Restoran Pondok Permai - Carens Tannia; Fenny Afrida (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study aims to examine the effect of Digitization and Human Resource Competence on the Financial Performance of Pondok Permai Restaurant. This study uses quantitative methods with multiple linear regression analysis. The sample consisted of 60 employees randomly selected based on certain criteria. Data were collected through observation, documentation, and questionnaires. The results showed that Digitization and HR Competence had a positive and significant effect on the Financial Performance of Pondok Permai Restaurant, both partially and simultaneously. These findings underscore the importance of digital transformation and human resource capacity building in driving the financial performance of Pondok Permai Restaurant in the digital era. The results of the hypothesis test in this study showed that the effect of digitization (the role of financial technology) on the financial performance of MSMEs (X1 → Y) showed significant results with a t-value of 4,089 > t-table 2,007. In addition, the relationship between HR competence and MSME financial performance (X2 → Y) was also proven to be significant, with t-value 7,358, and t-table 2,007. And the results of the analysis also prove that there is an indirect effect of digitization on financial performance through HR competence (X1 → X2 → Y), with an F-value of 329.463 > F-table 3.16. Overall, the results of this study strengthen the argument that the application of digital technology and the strengthening of human resources capacity is not only a trend, but a strategic need in optimizing the performance of MSMEs in the era of digital transformation.